Domestic fresh soft cheese from Bjelovar - Slavko Kirin (Mljekarstvo)
This paper shows results of organoleptic properties, physical-chemical composition and microbiological quality investigation of domestic fresh cheese samples taken from Bjelovar market (Croatia). The results were compared to research results obtained from other markets, published by other authors. The main characteristic is great variability that results in unequal quality. Weights of different samples ranged from 610 g to 830 g, with mean value 757.58 g. Cheese consistency shows even greater difference in variety ranging from soft fragmented (28.57 %) to firm fragmented (7.14 %). Odour was mostly pleasant and characteristic (71.43 %) and taste pleasant, slightly acidic, pure only in 57.14 % of samples. The most common failure in soft cheese organoleptic properties is noticed yeasty odour and taste. Mean value of dry matter was 23.42 g/100 g, and 25.29 g/100 g of fat in dry matter. Acidity of fresh cheese was in pH range from 4.45 to 3.81. Due to the fat content, fresh cheese from Bjelovar is a semi fat fresh cheese, while soft cheeses from researches of other authors are described as low fat cheeses (Pravilnik, 2007). Correlation factor for different characteristics was high. Microbiological analyses show that E. coli was in higher amounts than allowed in 3 of 14 samples, and S. aureus in 2 samples. Microbiological quality is also doubtful because of higher yeasts and mould quantity, which was also concluded by other authors mentioned in this paper.